2008
DOI: 10.1002/ange.200702287
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and Hemolytic Activities of Pyridinium Polymers as a Function of the Spatial Relationship between the Positive Charge and the Pendant Alkyl Tail

Abstract: Synthetic amphiphilic polymers that mimic the membranedisrupting properties of natural antimicrobial peptides [1] show potent biocidal activity towards bacteria, [2][3][4] fungi, [5] and viruses. [6] Their easy synthesis, stability towards enzymatic degradation, and facile chemical tailoring make them promising candidates as novel chemical disinfectants and nonleaching biocides for a variety of biomedical applications. However, there is a delicate balance between useful biocidal activity and detrimental toxici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 20 publications
2
52
0
1
Order By: Relevance
“…Apart from the ammonium groups, the iminium structures are another common form of the cationic groups, like pyridinium, [22][23][24][25] imidazolium 26,27 and guanidinium salts. 28,29 The difference between ammonium and iminium groups is that the positive charges of the latter ones are delocalized evenly through the π bonds or aromatic conjugated systems, which may influence their adsorptive ability to membrane.…”
Section: Monomer Designsmentioning
confidence: 99%
“…Apart from the ammonium groups, the iminium structures are another common form of the cationic groups, like pyridinium, [22][23][24][25] imidazolium 26,27 and guanidinium salts. 28,29 The difference between ammonium and iminium groups is that the positive charges of the latter ones are delocalized evenly through the π bonds or aromatic conjugated systems, which may influence their adsorptive ability to membrane.…”
Section: Monomer Designsmentioning
confidence: 99%
“…While there is not a complete understanding of all the factors influencing selectivity for eukaryotic and prokaryotic membranes, 46 it is likely that the particular hydrophilichydrophobic balance of the Et 3 P-BCP micelles results in its higher activity against red blood cell membranes. 55 Nevertheless, the overall results suggest that the phosphonium-functionalized micelles have good potential to selectively kill bacteria. While further studies would be required to elucidate the in vitro and in vivo toxicity, previous studies have shown that phosphonium compounds can exhibit low in vitro, 36,56 and in vivo 56 toxicity.…”
Section: Hemolysis Of Red Blood Cellsmentioning
confidence: 98%
“…Sen and co-workers adopted this approach to generate a series of random copolymers of 4-vinylpyridine and methacrylates ( Figure 12). 21 Sen prepared three different series via N-alkylation of the pyridinyl group: a) alkyl functionalised pyridinium-methyl methacrylate (same centre); b) methyl functionalised pyridinium-alkyl functionalised methacrylate (different centre); and c) alkyl functionalised pyridinium and methacrylate (same centre). This enabled Sen to compare amphiphilic polymers whose hydrophobic and cationic components were either spatially separated (single pendant; Fig.…”
Section: Poly(vinylpyridine)smentioning
confidence: 99%
“…Two series were designed: same centre -whereby the positive charge and alkyl group were on the pyridyl substituent; and separate centre -whereby the positive charge was located on the pyridine (methyl pyridinium ion) and the alkyl group incorporated on the acrylate centre. 21 For both series, MIC values decreased to an optimum alkyl tail length of C4 for E. coli and C6 for B. Figure 23 summaries the different lactam monomers used in these studies.…”
Section: Fig (20) Same Faced Different Centre Polyoxanorbornes (A)mentioning
confidence: 99%
See 1 more Smart Citation